Konflik antara Hak Asasi Manusia dan Kepentingan Publik dalam Penegakan Hukum Pidana: Studi Kasus Kontemporer - Karisma, Prayoga Teguh; Anggellina, Yunita Putri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Criminal law enforcement is a field that often faces complex challenges in balancing individual human rights with the broader public interest. This study examines in depth the comparison between human rights principles and the need to maintain public order in the context of criminal law enforcement. The author illustrates this conflict through contemporary criminal law case studies that reflect real-world situations. The research method used in this research is a descriptive qualitative method. Data collection techniques use content analysis techniques. The results of this research particularly highlight the ongoing tension between the protection of individual rights guaranteed by law and the urgent need to maintain social order required by society as a whole. By exploring this concept, this research contributes to a deeper understanding of how criminal law enforcement impacts human rights in the complex context of the modern world.